Strategic Integration of Using Questioning Strategies to Promote Students' Thinking Ability in English Foreign Language Learning (EFL) - Hermansyah Hermansyah; Rudi Hartono; Rahayu Puji Haryanti; Sri Wahyuni (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This study aims to investigate the role of questioning strategies in developing students’ cognitive and metacognitive skills in English as a Foreign Language (EFL) learning. Through a Systematic Literature Review (SLR) approach, relevant studies published between 2015 and 2025 were systematically identified and analyzed from databases such as Scopus, ERIC, Google Scholar, and ScienceDirect. The selected studies were evaluated based on the inclusion criteria, with a focus on questioning strategies, cognitive development, and metacognitive awareness. The analysis reveals that well-structured questioning, particularly open-ended, probing, and reflective types, significantly enhances learners’ higher-order thinking abilities—including analysis, evaluation, and synthesis—while also strengthening metacognitive processes such as planning, monitoring, and self-assessment. These questioning techniques foster a deeper understanding, promote independent learning, and encourage sustained engagement among EFL students. The findings indicate that high-level cognitive and reflective questions are the most effective in fostering critical and self-regulated learning. In conclusion, the study highlights that integrating systematic questioning into classroom instruction can foster critical thinking, enhance learning outcomes, and support students in developing into autonomous and reflective learners in EFL contexts.